Efficacy of ovarian tissue cryopreservation in a major European center - Bastings, Lobke; Liebenthron, J.; Westphal, J. R.; Beerendonk, C. C. M.; van der Ven, H.; Meinecke, B.; Montag, Markus; Braat, D. D. M.; Peek, R. (Journal of assisted reproduction and genetics, 2014)
To evaluate the effect of cryopreservation and thawing of ovarian tissue from oncological patients opting for fertility preservation on ovarian tissue viability.
Gesehen am 02.09.2020